Stable carbon isotopes of dissolved inorganic carbon in the Western North Pacific Ocean: Proxy for water mixing and dynamics - Ge, Tiantian; Luo, Chunle; Ren, Peng; Zhang, Hongmei; Fan, Di; Chen, Hongtao; Chen, Zhaohui; Zhang, Jing; Wang, Xuchen (Frontiers in Marine Science, 2022)
The uptake of atmospheric CO2 and the cycle of dissolved inorganic carbon (DIC) in the ocean are the major mechanisms and pathways controlling global climate change and carbon cycling. The stable carbon isotope (δ13C) of DIC, therefore, provides an important tracer for processes such as air-sea exchange, photosynthesis, and water dynamics in the ocean. Here, we present new δ13C-DIC data on water samples collected from a north-south transect (13°N-40°N, 150°E) in the western North Pacific (NP) Ocean in November 2019 and compare the results with those previously reported for similar transects (149.3°E) during WOCE and CLIVAR projects over the past three decades. The values of δ13C-DIC, ranging from -0.83‰ to 0.86‰, were higher in the surface waters and decreased with depth. The high δ13C-DIC values in the surface waters were influenced primarily by isotopic fractionation during air-sea exchange and photosynthesis. With depth, the movement of different water masses and mixing, as well as bathypelagic respiration in the dark water of the ocean, all play important roles in influencing the distribution and isotopic signatures of δ13C-DIC in the western NP Ocean. The δ13C-DIC values of the 0-200 m water layer varied from -0.17‰ to 0.86‰, with lower values at high latitudes, affected by the low δ13C-DIC values carried by the Oyashio Current to the Kuroshio Extension (KE) region. A downward trend was present in the δ13C-DIC signature from north to south in the North Pacific Intermediate Water (NPIW) and Pacific Deep Water (PDW) in the western NP, which reflected the remineralization of organic matter with a horizontal transport of NPIW and PDW. We found a strong 13C Suess Effect in the upper 2,000 m in the western NP Ocean, and δ13C-DIC at the surface (<50 m) has decreased by 0.60‰-0.85‰ since 1993. The mean δ13C-DIC change in the surface ocean was estimated at 0.28‰ per decade between 1993 and 2019. The air-sea exchange and water mixing in the study area may have accelerated the absorption of anthropogenic CO2 in recent years, which likely caused a slightly faster rate of decrease in the δ13C-DIC from 2005-2019 than that observed from 1993-2005.